Investigating the level of satisfaction of policyholders with supplementary health insurance in Iran - Asma Hamzeh; Nasrin Hozarmoghadam; Mitra Ghanbarzadeh (BMC, 2023)
Abstract The importance of customer satisfaction in business prosperity is undeniable, so many organizations consider customer satisfaction as the main driver of their business growth and try to keep their customers satisfied. The business market has never been so competitive in most areas. This is the reason why things like customer experience and customer loyalty are more and more important and are considered an indicator to measure the success of the business. Based on this, in this research, we will examine the level of satisfaction of insurance policyholders with supplementary health insurance services in Iran using the SERVQUAL model. This model is one of the most common models used in the field of quality assessment in the service sector. The method of conducting this research is a descriptive survey. The sampling method in the current research is simply random the statistical population is insurance policyholders and the sample number is 686 people from the society. The findings of the current research showed that there is a negative and significant gap in all dimensions of service quality.